Isolation of Pediococcus pentosaceus to compete Vibrio harveyi in the shrimp Litopenaeus vannamei hatchery - RUBIYANTO WIDODO HALIMAN; METHODIUS DIGNA KURNIA; MOHAMMAD NURUL IMAN; SATRIA AJI KUSUMA; BENI HALALLUDIN; RIFKY RIZKIANTINO; PUTRI PURNAMA SARI; MUFTI RAHAYU; RACHMAWATI NUR FITRIANA; BESTRAN VIRLANDO PANJAITAN; ADINDA KINASIH JACINDA; HENDRI LAIMAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Haliman RW, Kurnia MD, Iman MN, Kusuma SA, Halalludin B, Rizkiantino R, Sari PP, Rahayu M, Fitriana RN, Panjaitan BV, Jacinda AK, Laiman H. 2023. Isolation of Pediococcus pentosaceus to compete Vibrio harveyi in the shrimp Litopenaeus vannamei hatchery. Biodiversitas 24: 4514-4520. Shrimp is an aquaculture commodity with high economic value, and is widely cultured in Asia and South America. Among diseases in the shrimp hatchery, vibriosis is considered as the main problem, with emphasize on Vibrio harveyi infection. Probiotics are life microbes with defense mechanism against pathogens, and have been used in aquaculture as an alternative strategy in disease management through application into the water or through the feed. In order to renew the current probiotics available, exploration of probiotic candidate isolates with ability to compete with the luminous bacteria has been done in mangrove area of Merak Belantung, Kalianda, Lampung Province, Indonesia, and also from shrimp intestine, raised in the tank of research facility. Nine bacteria isolates were obtained from this exploration, and based on the references, 4 isolates had the potential to compete Vibrio harveyi. Based on the 16S rRNA sequencing result, those 4 isolates were Bacillus cereus, B. aryabhattai, Weisella paramesenteroides, and Pediococcus pentosaceus. Further analysis of in vitro test using agar-well diffusion inhibition method and in vivo test showed that among those 4 isolates, only P. pentosaceus had strong antibacterial activity against V. harveyi and could be used as probiotic in shrimp rearing with optimal dose at 5-10 µL L-1.